Yellow Future : Oriental Style in Hollywood Cinema - Park, Jane Chi Hyun (Book collections on Project MUSE., 2010)
Yellow Futurev examines the emergence and popularity of techno-oriental representations in Hollywood cinema since the 1980s, focusing on the ways East Asian peoples and places have become linked with technology to produce a collective fantasy of East Asia as the future. Jane Chi Hyun Park demonstrates how this fantasy is sustained through imagery, iconography, and performance that conflate East Asia with technology, constituting what Park calls oriental style. Park provides a genealogy of oriental style through contextualized readings of popular films-from the multicultural city in Blade Runne.